The Effects of Resveratrol and Apigenin on Jejunal Oxidative Injury in Ducks and on Immortalized Duck Intestinal Epithelial Cells Exposed to H2O2 - Ning Zhou; Yongqing Cao; Youwen Luo; Lihua Wang; Ruiqing Li; Heshuang Di; Tiantian Gu; Yun Cao; Tao Zeng; Jianping Zhu; Li Chen; Dong An; et al. (MDPI AG, 2024)
Oxidative stress increases the apoptosis of intestinal epithelial cells and impairs intestinal epithelial cell renewal, which further promotes intestinal barrier dysfunction and even death. Extensive evidence supports that resveratrol and apigenin have antioxidant, anti-inflammatory, and antiproliferative properties. Here, we investigated the ability of these two compounds to alleviate diquat-induced jejunal oxidative stress and morphological injury, using the duck as a model, as well as the effects of apigenin on oxidative stress induced by H2O2 in immortalized duck intestinal epithelial cells (IDECs). Ducks were randomly assigned to the following four groups, with five replicates: a control (CON) group, a diquat-challenged (DIQ) group, a resveratrol (500 mg/kg) + diquat (RES) group, and an apigenin (500 mg/kg) + diquat (API) group. We found that serum catalase (CAT) activity and total antioxidant capacity (T-AOC) markedly reduced in the RES and API groups as compared to the DIQ group (p < 0.05); moreover, serum S superoxide dismutase (SOD) levels increased significantly in the API group as compared to the DIQ group (p < 0.05). In jejunal mucosa, the malondialdehyde (MDA) content in the RES and API groups decreased more than that in the DIQ group (p < 0.05). In addition, the jejunal expression levels of the NRF2 and GCLM genes in the RES and API groups increased notably compared with those in the DIQ group (p < 0.05); meanwhile, CAT activity in the RES and API groups was markedly elevated compared with that in the CON group (p < 0.05). In IDECs, apigenin significantly restrained the H2O2-mediated increase in MDA content and decrease in CAT levels (p < 0.05). Furthermore, apigenin increased the protein expression of p-NRF2, NRF2, p-AKT, and p-P38; downregulated that of cleaved caspase-3 and cleaved caspase-9; and reduced the ratio of Bax/Bcl-2 in H2O2-treated IDECs (p < 0.05). In conclusion, resveratrol and apigenin can be used as natural feed additives to protect against jejunal oxidative stress in ducks.